Physicochemical parameters and functional properties of flours from advanced genotypes and improved cassava varieties for industrial applications - Chimphepo, L.; Alamu, Emmanuel Oladeji; Monjerezi, M.; Ntawuruhunga, P.; Saka, J.D.K. (Elsevier, 2021)
Cassava has potential for many industrial uses, which provide an opportunity for more rewarding markets. Therefore, significant research on improved varieties, targeting industrial applications, is required as a possible approach to spur improvements in the value chain. To this end, this study evaluated the physicochemical parameters and functional properties of ten (10) improved cassava genotypes for fast-tracking adaptable and preferred cassava genotypes for industrial use. The genotypes were collected from a multi-location (Uniform yield Trial) trial of the IITA breeding program in Malawi. Their flour samples were analysed for various physicochemical parameters and functional properties compared with currently marketed High Quality Cassava Flour (HQCF). Results show that genotype effect on overall quality characteristics endearing to industrial applications was significant, allowing identification of industry preferred genotypes. Starch and amylopectin content are the major determinants of variability in the cassava flours' functional properties, such as water and oil absorption capacities, solubility, and swelling power. Overall, genotypes I020452 and I010040, and the released variety Sagonja have a high starch and amylopectin content, high bulk density, and all the analysed functional properties. These genotypes showed comparable/or superior functional properties to market HQCF.